al-Akhṭā’ fī Istikhdām al-Af‘āl al-Mujarradah wa-al-Af‘āl al-Mazīdah fī al-Jumal al-Basīṭah ladá Ṭullāb Qism Ta‘līm al-Lughah al-‘Arabīyah, Jāmi‘at Jākartā al-Ḥukūmīyah - Muhammad Kamal bin Abdul Hakim; Romdani; Maulidah Hasanah (Universitas Negeri Jakarta, 2019)
This study aims to factually get data about the form of mistakes in the use of al-fi‘l al-mujarrad and al-fi‘l al-mazīd as well as the percentage of the mistakes including the types of mistakes done by the students and its causes. The study was conducted in the Arabic Language Education Study Progam, Universitas Negeri Jakarta in the academic year (107) of 2017–2018. For students of 2015. The data of this study are students answer papers about the use of al-fi‘l al-mujarrad and al-fi‘l al-mazīd with the amount of 44 questions with the 35 samples that randomly chosen. The method of this study is descriptive with the procedures: collecting data, identifying the mistakes, classifying the mistakes, describing the mistakes, and interpreting the mistakes. Based on the result, out of 1540 answers, there are 701 mistakes at the 1st meeting and 647 mistakes at the 2nd meeting including (1) mistakes in the use of al-thulathī al-mujarrad with an average of 177,5 mistakes; (2) mistakes in the use of al-rubā‘ī al-mujarrad with an average of 42 mistakes; (3) mistakes in the use of al-thulāthī al-mazīd bi-ḥarf with an average of 108 mistakes; (4) mistakes in the use of al- thulāthī al-mazīd bi-ḥarfayn with an average of 140,5 mistakes; (5) mistakes in the use of al-thulāthī al-mazīd bi-thalāthah aḥruf with an average of 129 mistakes; (6) mistakes in the use of al-rubā‘ī al-mazīd bi-ḥarf with an average of 27 mistakes; (7) mistakes in the use of al-fi‘l al-rubā‘ī al-mazīd bi-ḥarfayn with an average of 52 mistakes. From all mistakes mentioned above, the highest mistakes in the use of al-fi‘l al-rubā‘i al-mujarrad with an average of 42 mistakes.